Recruitment of babies in vaccine trial: A challenge - Hanumante, Neeta Milind; Ransubhe, Sampada Pramod (Indian Journal of Child Health, 2019)
Introduction: The enrollment of children into clinical trials is challenging. India is increasingly recognized as a site for clinical research due to its large population and growing research capabilities, though data regarding barriers for recruitment into pediatric vaccine clinical trials are scarce. Objective: The objective of this study was to assess the barriers in recruitment and to find out parental factors for non-participation of their babies in the vaccine clinical trial. Materials and Methods: This was a prospective cross-sectional non-interventional study which was carried out in the pediatric clinical research unit of a tertiary care multispecialty teaching hospital in Pune. The study social worker visited postnatal ward to prime mothers regarding the pneumococcal vaccine clinical trial. Parents of babies aged 6–8 weeks, who were eligible for participation in the ongoing pneumococcal vaccine trial were explained the informed consent form of this clinical trial and their willingness for participation was sought. The reason for refusal of the parents, who declined the study participation of their baby, was documented. Results: Even though eligible inborn baby pool was large (n=384), only 148 (38.54%) inborn babies were brought to our clinical research unit showing a major barrier in the recruitment. Of 204 babies who presented to clinical research unit, 94 babies (46.08%) were enrolled in the ongoing clinical trial and the majority of them were inborn (89.36%), whereas only 10 of 56 (17.86%) outborn babies were enrolled. There was no gender difference noted in enrolled versus non-enrolled babies. There was no significant association between baby’s gender and place of delivery. The major reasons for non-enrollment were “unwillingness” for participation in clinical trial (68.18%) followed by mothers going outstation, staying far away from our hospital, lack of time, and concerns due to research vaccine. Conclusion: Our study has shown that even though eligible inborn baby pool was large, only 38.54% of inborn babies were brought to our clinical research unit, thus a major barrier in recruitment. More effective counseling and recruitment strategies are needed to scale up the enrollment more so for the outborn babies.